Chatbots: An Analysis of the State of Art of Literature - Bernardini, Andréia Ana; Sônego, Arildo A.; Pozzebon, Eliane (Anais do Workshop on Advanced Virtual Environments and Education (WAVE), 2018)
Considering the context of Computer Science, Chatbots are computer programs that, through techniques of Artificial Intelligence, aim to simulate human behavior when at the moment of a dialogue through text messages. Despite being a relatively new area of study, the application of this concept has increased considerably, whether in academic settings or in commercial applications, such as situations involving assistants to clarify doubts on websites of manufacturers of electronic products or even in services such as telephony. Thus, this article proposes an analysis of the state of the art of research through a quantitative bibliometric analysis, supported by the Scopus database.